Diffusion tensor imaging revealed different pathological processes of white matter hyperintensities - Min, Zhi-gang (BMC Neurol, 2021)
BACKGROUND: Although increasing evidence showed the correlations between white matter hyperintensities (WMHs) and cognitive impairment, the relationship between them is still modest. Many researchers began to focus on the variation caused by the heterogeneity of WMH. We tried to explore the pathological heterogeneity in WMH by using diffusion tensor imaging (DTI), so as to provide a new insight into the future research. METHODS: Diffusion weighted images (DWIs) of the brain were acquired from 73 patients with WMH and 18 healthy controls, which were then modeled by DTI. We measured fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD) of white matter of the periventricular frontal lobe (pFL), periventricular occipital lobe (pOL), periventricular parietal lobe (pPL) and deep centrum ovales (dCO), and grouped these measures according to the Fazekas scale. Then we compared the DTI metrics of different regions with the same Fazekas scale grade. RESULTS: Significantly lower FA values (all p < 0.001), and higher MD (all p < 0.001) and RD values (all p < 0.001) were associated with WMH observed in the periventricular frontal lobe (pFL) compared to all other regions with the same Fazekas grades. The AD of WMH in the pFL was higher than that of pPL and dCO, but the differences between groups was not as high as of MD and RD, as indicated by the effect size. In the normal control group, DTI metrics between pFL and other regions were not significantly different or less significant different. The difference of DTI metrics of WMH between pPL, pOL and dCO was lower than that of normal white matter, as indicated by the effect size. CONCLUSION: Distinct pathological processes can be revealed by DTI between frontal periventricular WMH and other regions. These processes may represent the effects of severe demyelination within the frontal periventricular WMH. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12883-021-02140-9.